Evaluation of Anti-biofilm Formation of Methicillin Resistant Staphylococcus Species in Clinical Milk Samples of Bovine Mastitis using Selective Medicinal Plants - Chockalingam, Jayaprabha; Balasubramanian, Akshaya; Krishnasamy, Jai Santhosh Krishnan; Balasundaram, Karthika; Sivasamy, Kavin Kumar; Manohar, Anusree; Sagayaraj, Joval Antony Martin; Ramasamy, Suganthi (Asian Journal of Biological and Life Sciences)
Staphylococcus aureus is a Gram positive bacterium which is a member of the firmicutes is the most considered causative agent for bovine mastitis in dairy herds worldwide. The Clinical milk samples were collected from the glycerol stock. After subculture, the confirmation of Staphylococcus species was performed using Selective agar plate method, Gram staining and Biochemical characterization. Antibiotic susceptibility test was performed for the predominant culture of Staphylococcus aureus to determine the organism’s resistance, susceptibility or intermediate towards certain antibiotics. The screening for Methicillin Resistance Staphylococcus aureus was performed using HI chrome Rapid Methicillin Resistant Staphylococcus aureus agar base media. The detection of biofilm forming ability in the isolates was performed using different phenotypic assays. Three different medicinal plants (Erythrina variegata, Cissus quadrangular is and Vitex negundo) were selected for the study and used for the preparation of methanol, Chloroform and aqueous extracts. The extracts were then subjected for the qualitative and quantitative photochemical analysis. The determination of the lowest concentration of the plant extracts in inhibiting the growth of the organism (Antibiofilm formation) by Minimum Inhibitory Concentration and Minimum Bacterial Concentration in MRSA were found to have higher sensitivity to the methanol extracts and resistant to the chloroform and aqueous extracts.
Keywords: Biofilm; Bovine mastitis; Medicinal plants; Minimum inhibitory concentration and Minimum Bacterial concentration.; MRSA; Staphylococcus Aureus